Fig. 3 in Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica - Kuzmina, T. A.; Dykyy, I. V.; Salganskij, O. O.; Lisitsyna, O. I.; Korol, E. M.; Kuzmin, Yu. I. (Zenodo, 2021)
Fig. 3. Proportion (in %) of helminth species parasitize five Antarctic teleost fishes off the area of the UAS "Akademik Vernadsky" on larval and adult stages. Published as part of Kuzmina, T. A., Dykyy, I. V., Salganskij, O. O., Lisitsyna, O. I., Korol, E. M. & Kuzmin, Yu. I., 2021, Helminth Diversity In Teleost Fishes From The Area Of The Ukrainian Antarctic Station "Akademik Vernadsky", Argentine Islands, West Antarctica, pp. 251-264 in Zoodiversity 55 (3) on page 258, DOI:10.15407/zoo2021.03.251, http://zenodo.org/record/6455979